Review Article : Implikasi Suplemen Asam Folat Prenatal terhadap Risiko Autism Spectrum Disorder (ASD) pada Keturunannya - Diah Muldianah; Indah Laily Hilmi; Salman Salman (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Folic acid plays an important role for the health of mothers and babies, especially in the growth and development of the fetus. Based on several previous studies, it was found that prenatal folic acid deficiency or excess can increase the risk of Autism Spectrum Disease (ASD) in infants. This raises concerns about the adverse effects of prenatal folic acid supplements including an increased risk of ASD. Therefore, this literature review article was created to further explore the implications or involvement of maternal folic acid supplementation on the risk of ASD in their offspring. The Google Scholar, Pubmed, and Connected Papers electronic databases were used to find literature that met the criteria. The results of this review found a potential beneficial effect of prenatal folic acid supplementation on the risk of developing ASD, although conflicting results have been reported. In summary, this literature review article demonstrates that prenatal folic acid supplementation can significantly reduce the risk of ASD in offspring compared to women without prenatal folic acid supplementation.